Immune Checkpoints in Circulating and Tumor-Infiltrating CD4+ T Cell Subsets in Colorectal Cancer Patients - Toor, Salman M.; Murshed, Khaled; Al-Dhaheri, Mahmood; Khawar, Mahwish; Abu Nada, Mohamed; Elkord, Eyad (Frontiers in Immunology, 2019)
Blockade of inhibitory immune checkpoints (ICs) is a promising therapeutic approach; however, it has shown limited success in some cancers including colorectal cancer (CRC). The tumor microenvironment (TME) is largely responsible for response to therapy, and its constituents may provide robust biomarkers for successful immunotherapeutic approaches. In this study, we performed a phenotypical characterization and critical analyses of key inhibitory ICs and T regulatory cell (Treg)-related markers on CD4+ T cell subsets in CRC patients, and compared with normal colon tissues and peripheral blood from the same patients. We also investigated correlations between the levels of different CD4+ T cell subsets and the clinicopathologic features including disease stage and tumor budding. We found a significant increase in the levels of CD4+FoxP3+Helios+ T cells, which represent potentially highly immunosuppressive Tregs, in the CRC TME. Additionally, tumor-infiltrating CD4+ T cells upregulated programmed cell death protein-1 (PD-1), cytotoxic T-lymphocyte-associated protein-4 (CTLA-4), T cell immunoglobulin and mucin domain-3 (TIM-3) and lymphocyte-activation gene 3 (LAG-3). We also characterized the expression of PD-1, CTLA-4, TIM-3 and LAG-3 on different CD4+FoxP3-/+Helios-/+ T cell subsets. Interestingly, we found that CTLA-4, TIM-3 and LAG-3 were mainly co-expressed on FoxP3+Helios+ Tregs in the TME. Additionally, FoxP3high Tregs expressed higher levels of Helios, CTLA-4 and TIM-3 than FoxP3low T cells. These results highlight the significance of Tregs in the CRC TME and suggest that Tregs may hamper response to IC blockade in CRC patients, but effects of different IC inhibition regimes on Treg levels or activity warrants further investigations. We also found that CD4+CTLA-4+ T cells in circulation are increased in patients with advanced disease stage. This study simultaneously provides important insights into the differential levels of CD4+ T cell subpopulations and IC expression in CRC TME, compared to periphery and associations with clinicopathologic features, which could be used as potential biomarkers for CRC progression and response to therapy.